Factors that Contribute to the Achievement of Sustainability in Private Universities of Malaysia. - Basu Govindaraju; John Jeyasingam; Md. Mamun Habib; Uvarani Letchmana; Ravindran Rathakrishnan (International Journal of Supply Chain Management, 2018)
Abstract: Sustainability is todays most important benchmarking criteria to measure performance in organisations. Thus, the measure of critical sustainable practices plays a vital role in determining sustainable performance. This research paper attempts to identify fundamental dimensions of sustainable practices which contribute to sustainable performance in private universities of Malaysia. In line with this, Exploratory Factor Analysis (EFA) was carried out to identify fundamental constructs that define the sustainable performance of private universities (PUs). A series of pre and post analysis were conducted using survey questionnaire to draw inferences on the topic. The EFA technique was used to regroup the components related to indicators of sustainable practices into a limited set of components based on shared variance. EFA is generally used to sum up data so that relationships and patterns among constructs can be easily understood and interpreted. Eventually, four factor constructs emerged in this study. Theseoffered a meaningful relationship pattern which contributed to the sustainable performance indicators of private universities in Malaysia.